Principal Leadership Moderates Motivation And Work Diciplin Effects On Teachers Performance - Lafi Yulifah, 1352020072; Basiya, Robertus (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the effect of motivation and work dicipline on the performance of KesatrianÂ  senior high school teachers Semarang under the principals leadership as a moderation variable. In this research, the population is about 101 respondents and uses explanatory research with the criteria of Kesatrian 2 Senior High Schoolâs teachers Semarang. The measurement use a likert scale of five alternative answers. Test instruments being used are validity and reliability, while normality test uses Kolmogorov Smirnov Statistic Test. Heteroskedasrisitas Test using Glejser method, the test model use the coefficient of determination (Adjust R Square) and F test (Good ness of Fit), whereas hypothesis test uses regression analyze with t-test on significant rate 0f 0,05. Based on the results of the study, it can be summarized as follows:Â  Motivation has positif and signification effect on teacher performance, Work Discipline has positif and signification effect on teacher performance, The principal leadership doesnât have Â effect on teacher performance, The principal leadership role doesnât moderate Â influence of motivation on teacher performance, andÂ  The principals leadership role doesnât moderate Â influence work discipline on teacher performance Keywords: Principal Leadership, Motivation, Discipline, and Â TeachersÂ  Â Performance